Characterization and optimization of lyophilization and storage conditions of Leech saliva extract from the tropical leech Hirudinaria manillensis - Abdualkader, Abdualrahman Mohammed; Mohammad Ghawi, Abbas; Alaama, Mohamed; Awang, Mohamed; Merzouk, Ahmed (Faculty of Pharmacy, University of Karachi, 2013)
The medicinal Malaysian leeches have been used in traditional medicine to treat many different ailments. In this study, leech saliva extract (LSE) was collected from the medicinal Malaysian leech Hirudinaria manillensis. Gel electrophoresis of LSE was carried out to estimate the peptide and protein molecular weights of its content. Results showed that LSE contains more than 60 peptides and proteins with molecular masses ranging from 1.9-250kDa. Thrombin time assay in vitro was employed to assess the collected LSE antithrombin activity. First, to study its stability, LSE was lyophilized under the following different conditions: pre-freezing temperature, type of container and lyophilization cycle. Pre-freezed LSE sample at -20°C and lyophilized for 24 hours retained about 100-95% of its original biological activities. Second, the LSE antithrombin activity was monitored for a period of six months. Storage temperature, type of the container and photosensitivity effects on antithrombin activity of the lyophilized (solid state) and non-lyophilized (liquid state) were investigated. Results showed that storage temperature drastically affected the biological activity of LSE with -20 °C as the optimum temperature. Samples stored at ambient temperature and +4 °C were light photosensitive and adversely affected when stored in polypropylene tubes. Lyophilized samples were more stable than non-lyophilized ones over the period of study. To sum up, in order to have a biologically active stock of LSE, it has to be lyophilized for no more than 24 hours following freezing at -20°C and has to be stored at -20°C in glass tubes protected from light.